ASXL1 mutations are frequent and prognostically detrimental in CSF3R‐mutated chronic neutrophilic leukemia. Issue 7 (July 2015) - Elliott, Michelle A.; Pardanani, Animesh; Hanson, Curtis A.; Lasho, Terra L.; Finke, Christy M.; Belachew, Alem A.; Tefferi, Ayalew
<x xml:space="preserve">Abstract</x> Colony stimulating factor 3 receptor gene (CSF3R) mutations have recently been associated with chronic neutrophilic leukemia (CNL). Fourteen patients with CSF3R‐mutated CNL (median age 67 years; 57% males) were screened for additional mutations; 8 (57%) and 5 (38%) harbored an ASXL1 and/or SETBP1 mutation (two patients expressed both), respectively. Two patients developed blastic transformation, both SETBP1‐mutated and ASXL1‐unmutated, whereas two other cases evolved into chronic myelomonocytic leukemia (CMML), both ASXL1‐mutated and SETBP1‐unmutated. Median survival was 23.2 months (10 deaths documented). On multivariable analysis mutated ASXL1 (P = 0.009; HR 19.6, 95% CI 2.1–184.1) and thrombocytopenia (P = 0.005; HR 28.8, 95% CI 2.8–298.2) were independently predictive of shortened survival. This study provides information on the natural history of CSF3R‐mutated CNL and identifies mutant ASXL1 and thrombocytopenia as risk factors for survival. The study also suggests pathogenetic roles for SETBP1 and ASXL1 mutations in disease evolution into blast phase disease and CMML, respectively. Am. J. Hematol. 90:653–656, 2015. © 2015 Wiley Periodicals, Inc.